Analisis Status Gizi Mahasiswi Gizi Universitas Aisyah Pringsewu Berdasarkan Indeks Massa Tubuh (IMT) dan Lingkar Lengan Atas (LILA) - Khairani, Masayu Dian; Muharramah, Alifiyanti; Lestari, Lara Ayu; Nurhayati, Aftulesi; Velina, Risti (Jurnal Gizi Aisyah, 2024)
Nutritional status reflects the balance between nutrient intake from food and the body's metabolic needs. Students, as a productive age group transitioning from adolescence to adulthood, have specific nutritional requirements depending on age, gender, body weight, and height. This study aims to assess the nutritional status of female students in the Nutrition Study Program at Aisyah Pringsewu University by screening weight, height, and upper arm circumference. The indicators used are Body Mass Index (BMI) and Upper Arm Circumference (UAC). This quantitative descriptive research with a cross-sectional method was conducted in March 2024. The research subjects consisted of 50 second-semester female students aged >18 years selected using purposive sampling technique. The results showed that 60% of the students had normal nutritional status based on BMI, 24% were overweight, and 16% were underweight. Based on UAC, 76% had normal nutritional status and 24% experienced Chronic Energy Deficiency (CED). These findings indicate the need for tailored nutritional education approaches considering the students' age characteristics to support their nutritional well-being, given the potential health issues that may arise.